2018
DOI: 10.1093/ibd/izx102
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Dysplasia and Colorectal Cancer Observed among Inflammatory Bowel Disease Patients with Prolonged Colonic Diversion

Abstract: Diverted dysplasia occurred infrequently with rates overlapping those reported in registries for IBD-based rectal cancers. Neoplasia was undetected in patients with < 10 pyd, regardless of diversion duration, suggesting low yield for endoscopic surveillance before this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 33 publications
(56 reference statements)
0
27
0
Order By: Relevance
“…Besides, the following conditions have been reported as characteristics of CD-associated CRC: patients were approximately 10 years younger than those with typical CRC, had a long duration of CD (10-20 years), in many cases, cancer developed in the right colon, the histologic type was mucinous adenocarcinoma, and cancer was likely to develop in lesions caused by CD [15][16][17]. Bettner et al reported that while the risk of CRC in in ammatory bowel disease (IBD) populations have been well described, there is a lack of data on the risk of CRC in diverted IBD bowel segments [1]. We believe that our cases can be included in this category.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, the following conditions have been reported as characteristics of CD-associated CRC: patients were approximately 10 years younger than those with typical CRC, had a long duration of CD (10-20 years), in many cases, cancer developed in the right colon, the histologic type was mucinous adenocarcinoma, and cancer was likely to develop in lesions caused by CD [15][16][17]. Bettner et al reported that while the risk of CRC in in ammatory bowel disease (IBD) populations have been well described, there is a lack of data on the risk of CRC in diverted IBD bowel segments [1]. We believe that our cases can be included in this category.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that our cases can be included in this category. Few studies focusing on diverted CRC have been published, and based on these reports, only a small percentage of cases have been identi ed [1,[18][19][20][21][22]. These are summarized in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crohn's disease (CD)-related anorectal cancer following fecal diversion is a rare disease. Although the risk of colorectal cancer (CRC) has been well described, the risk of CRC in diverted bowel segments is lacking, and the current risk remains unclear [ 1 ]. Typically, CD-associated cancers present in advanced stages are poorly differentiated and have a worse prognosis than usual adenocarcinoma [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%